Funcionalização de 5-iodo-1,2,3-triazóis e síntese de seleno- e tioésteres por meio de reações de acoplamento carbonilativo empregando monóxido de carbono gerado ex situ - Albuquerque, Danilo Yano de (2022)
The use of pressurized carbon monoxide (CO) gas cylinders can lead to serious risks during their handling. Hence, the demand for safer carbonylation methods has been gradually increasing with the use of different techniques or CO-realeasing molecules. In the first chapter, we report a simple and direct palladium-catalyzed aminocarbonylation of 5-iodo-1,2,3-triazoles backbone for the incorporation of an amide functional group by employing an alternative source of carbon monoxide generated ex situ by dehydration of formic acid in sulfuric acid (Morgan’s reaction). The reaction was performed in a two-chamber system (COware) providing the synthesis of 26 compounds with yields up to 98% by using different primary amines and 5-iodo-1,2,3-triazoles. The methodology developed exhibited a series of advantages, such as simplicity, short reaction time, high yields, the use of dimethyl carbonate as a sustainable solvent, and the use of efficient alternative source of carbon monoxide, avoiding pressurized cylinder. The chapter 2 is focused on the development of a new catalytic protocol for the synthesis of seleno- and thioesters from a palladium-catalyzed carbonylative coupling reaction between aryl iodides and nucleophilic selenium and sulfur sources, which were obtained by in situ reductive cleavage of diorganoyl dichalcogenides with the assistance of zinc metal. This approach exhibited good functional group tolerance, allowing the synthesis of 30 compounds with yields up to 97%. Interestingly, aryl iodides carrying electron-withdrawing groups showed slower reactivity than those with electron-donating counterparts, affording the products with lower yields. For these cases, it was necessary to increase the amount of carbon monoxide to improve the reaction yield. The important features of this methodology include mild reaction conditions, the use of efficient alternative source of carbon monoxide, avoiding pressurized cylinder, and avoids the use of selenols and thiols, which are difficult-to-handle, easily oxidized, and have the unpleasant odor.